2014
DOI: 10.1371/journal.pone.0086270
|View full text |Cite
|
Sign up to set email alerts
|

Participation of Candida albicans Transcription Factor RLM1 in Cell Wall Biogenesis and Virulence

Abstract: Candida albicans cell wall is important for growth and interaction with the environment. RLM1 is one of the putative transcription factors involved in the cell wall integrity pathway, which plays an important role in the maintenance of the cell wall integrity. In this work we investigated the involvement of RLM1 in the cell wall biogenesis and in virulence. Newly constructed C. albicans Δ/Δrlm1 mutants showed typical cell wall weakening phenotypes, such as hypersensitivity to Congo Red, Calcofluor White, and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
58
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(66 citation statements)
references
References 61 publications
7
58
0
1
Order By: Relevance
“…Here, it was observed that the C . albicans strain used in this study could produce hyphae under unstressed and stressed situations, as previously demonstrated [114] which could contribute to its high resilience towards antimicrobial treatment and posterior consecutive recoveries of its regrowth aptitude.…”
Section: Discussionmentioning
confidence: 59%
“…Here, it was observed that the C . albicans strain used in this study could produce hyphae under unstressed and stressed situations, as previously demonstrated [114] which could contribute to its high resilience towards antimicrobial treatment and posterior consecutive recoveries of its regrowth aptitude.…”
Section: Discussionmentioning
confidence: 59%
“…1). Next, we tested the sensitivity of these deletants to SDS, a detergent usually employed to determine the compactness of the cell wall, since less compact cell wall would allow SDS to readily reach and damage the plasma membrane resulting in cell death945. Scsur4 Δ/Δ strain was found to be SDS-sensitive (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Among antifungals that target cell wall, echinocandins and nikkomycin inhibit β-Glucan synthesis and chitin synthesis, respectively. Defective cell wall biogenesis is known to attenuate infections by C. albicans 910. Thus, a better understanding of cell wall biogenesis and integrity may reveal novel targets for antifungal drug development.…”
mentioning
confidence: 99%
“…In S. cerevisiae and C. albicans, RLM1 has been shown to play key roles in CWI (Dodou and Treisman 1997;Watanabe et al 1997;Delgado-Silva et al 2014). In filamentous fungi, information concerning the involvement of rlm-1 in cell wall remodeling is less clear and in some cases even contradicting (Damveld et al 2005;Fujioka et al 2007, Kovacs et al 2013.…”
Section: Discussionmentioning
confidence: 99%
“…In various other fungi, Rlm1 has been shown to be involved in the regulation of expression of some cell wall-related biosynthetic enzymes (Damveld et al 2005;Kovacs et al 2013;Levin 2011;Delgado-Silva et al 2014), yet the involvement of Rlm1p homologs in the CWI pathway in filamentous fungi is by far less clear than that established in S. cerevisiae.…”
Section: Introductionmentioning
confidence: 99%